How to Operationalize IMF Engagement on Social Spending during and in the aftermath of the COVID-19 Crisis - Yackovlev, Irene (IMF How To Notes; How-To Note, 2020)
How to Operationalize IMF Engagement on Social Spending during and in the aftermath of the COVID-19 Crisis.